Israel's banking system: annual survey - Bank of Israel (Jerusalem Bank of Israel, 1988)
​The Annual Surveys of Israel's Banking System analyze developments in the banking system with regard to activity, business results and risks, the structure of the system, and the activity of the Banking Supervision Department. The reports are illustrated with diagrams and contain text tables, as well as a statistical appendix containing detailed data which helps researchers and analysts to analyze trends in Israel's banking system.
1990, 1993-1995 are not available at the library
Keywords: Banks and Banking; BANKS; SURVEYS; ISRAEL